2021 U.S. Virgin Islands Zika health brigade: Providing recommended pediatric health screenings for children born to mothers with laboratory evidence of possible Zika virus infection during pregnancy. Issue 5 (27th December 2022) - de Wilde, Leah H.; Harrison, Cosme Jeremy; Ceesay, Binta E.; Mayers, Charmaine S.; Ferrol‐Hawley, Janney; Canton, Jacqueline; Godfred‐Cato, Shana; Reynolds, Megan R.; Brown‐Shuler, Lessely; Randhawa, Sukhdeep; Schoelles, Dan; Hillman, Braeanna; et al.
Abstract: Background: The United States Virgin Islands (USVI) Department of Health (DOH) conducted a second Zika health brigade (ZHB) in 2021 to provide recommended Zika‐related pediatric health screenings, including vision, hearing, neurologic, and developmental screenings, for children in the USVI. This was replicated after the success of the first ZHB in 2018, which provided recommended Zika‐related pediatric health screenings to 88 infants and children exposed to Zika virus (ZIKV) during pregnancy. Methods: Ten specialty pediatric care providers were recruited and traveled to the USVI to conduct the screenings. USVI DOH scheduled appointments for children included in CDC's U.S. Zika Pregnancy and Infant Registry (USZPIR). During the ZHB, participants were examined by pediatric ophthalmologists, pediatric audiologists, and pediatric neurologists. We report the percentage of participants who were referred for additional follow‐up care or given follow‐up recommendations in the 2021 ZHB and compare these referrals and recommendations to those given in the 2018 ZHB. Results: Thirty‐three children born to mothers with laboratory evidence of ZIKV infection during pregnancy completed screenings at the 2021 ZHB, of which 15 (45%) children were referred for additional follow‐up care. Ophthalmological screenings resulted in the highest number of new referrals for a specialty provider among ZHB participants, with 6 (18%) children receiving referrals for that specialty. Speech therapy was the most common therapy referral, with 10 (30%) children referred, of which 9 (90%) were among those who attended the 2018 ZHB. Conclusions: Thirty‐three children in a jurisdiction with reduced access to healthcare specialists received recommended Zika‐related pediatric health screenings at the ZHB. New and continuing medical and developmental concerns were identified and appropriate referrals for follow‐up care and services were provided. The ZHB model was successful in creating connections to health services not previously received by the participants.